Load-power relationship in older adults: The influence of maximal mean and peak power values and their associations with lower and upper-limb functional capacity - Marques, Diogo Luís; Neiva, Henrique Pereira; Marinho, Daniel Almeida; Pires, Ivan Miguel; Nunes, Célia; Marques, Mário Cardoso (Frontiers in Physiology, 2022)
Identifying the relative loads (%1RM) that maximize power output (Pmax-load) in resistance exercises can help design interventions to optimize muscle power in older adults. Moreover, examining the maximal mean power (MPmax) and peak power (PPmax) values (Watts) would allow an understanding of their differences and associations with functionality markers in older adults. Therefore, this research aimed to i) analyze the load-mean and peak power relationships in the leg press and chest press in older adults, ii) examine the differences between mean Pmax-load (MPmax-load) and peak Pmax-load (PPmax-load) within resistance exercises, iii) identify the differences between resistance exercises in MPmax-load and PPmax-load, and iv) explore the associations between MPmax and PPmax in the leg press and chest press with functional capacity indicators. Thirty-two older adults (79.3±7.3 years) performed the following tests: medicine ball throw (MBT), five-repetition sit-to-stand (STS), 10-meters walking (10W), and a progressive loading test in the leg press and chest press. Quadratic regressions analyzed i) the load-mean and peak power relationships and identified the MPmax-load, MPmax, PPmax-load, and PPmax in both exercises, ii) the associations between MPmax and PPmax in the chest press with MBT, and iii) the associations between MPmax and PPmax in the leg press with STSpower and 10Wvelocity. In the leg press, the MPmax-load was 66% 1RM, and the PPmax-load was 62% 1RM, both for women and men (p>0.05). In the chest press, the MPmax-load was 62% 1RM, and the PPmax-load was 56% 1RM, both for women and men (p>0.05). There were differences between MPmax-load and PPmax-load within exercises (p<0.01) and differences between exercises in MPmax-load and PPmax-load (p<0.01). The MPmax and PPmax in the chest press explained 48% and 52% of the MBT-1kg and MBT-3kg variance, respectively. In the leg press, the MPmax and PPmax explained 59% of STSpower variance; however, both variables could not explain the 10Wvelocity performance (r2 0.02). This study shows that the Pmax-load is similar between sexes, is resistance exercise-specific, and varies within exercises depending on the mechanical power variable used in older adults. Furthermore, this research demonstrates the influence of the MBT as an upper-limb power marker in older adults.